Strength training for children and adolescents: A progression to future health and performance - McEntyre, A. S. (Journal of Australian Strength and Conditioning, 2018)
Strength training with correct programming and supervision from qualified and experienced coaches is a safe and effective method of improving health and athletic performance for both children and adolescents.